The Tarbiyah Ruhiyyah Curriculum of Isy Karima Qur'anic Memorization Boarding School, Karanganyar, Central Java - Muhammad Jihad; Sigit Wibowo; Widyasari (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
It has been observed that some Qur'an memorizers do not demonstrate the expected performance. Some of them merely memorise without ensuring harmony between the quality of their deeds and noble character on the one hand, and the progress of their memorisation on the other. The cause is the inadequacy of tarbiyah ruhiyah which effectively internalizes the values ​​contained in the Qur'an within oneself. This study aimed to explore the tarbiyah ruhiyah curriculum implemented at Ma'had Tahfizhul Qur'an Isy Karima by employing a descriptive qualitative research method in the form of a field study. Data was collected through observation, interviews and documentation. The collected data was analyzed through the stages of reduction, presentation, and drawing conclusions. The finding indicated that the Qur'an memorization education concept at Ma'had Tahfizhul Qur'an Isy Karima was considered ideal, as it was supported by a strong tarbiyah ruhiyah curriculum. This curriculum encompassed objectives, contents, methods, and evaluation. Therefore, this curriculum is recommended for implementation in Islamic educational institutions focusing on Qur'an memorization, particularly those based in Islamic boarding schools, as its design is derived from the Islamic boarding school system.